(untitled) (Al-Qamar, 2022)
Sadat Hassan Manto is known as leading and renowned short story writer. He earned lot popularity through his unique writings and. He was badly criticized in the literary circles throughout his life but he depicted the real picture of the women of the society particularly, and done his job very successfully. In this article his ideas about the partition are highlighted as per his conviction towards Indo-Pak division in the history. It is proved in the article that he was justified his idea about humanity and social moral values of the society which was much more acknowledged after his death and he is known as worldwide famous writer in the history of literature. In this paper his valuable status is being described in the light of his writings.